The Critical Discourse Analysis of Language Teacher’s Instructional Decisions - Youwen, Zhang (International Journal of Educational Technology and Learning, 2018)
Teacher’s decision making is an instant indicator of the discourse activities in the context of education. A critical discourse analysis of the language teacher’s classroom decisions is able to give an insight into the essence of discourse of teacher authority, power, and morality sneaking in classroom teaching at the micro and macro levels, and then understand the force that the hidden power of discourse relations acts on the subject and the object of teaching in the field of educational discourse, the way school discourse communicates as well, hoping teachers, students, language, knowledge being in harmony and free in the context of education.